The Role of Institutions and Culture in Shaping Law and Morality - Vebritha, Silvy (Legalis : Journal of Law Review, 2024)
This narrative review explores the dynamic interplay between legal positivism and natural law within contemporary legal systems, emphasizing their convergence in contexts of legal pluralism. The study aims to analyze how law and morality intersect and influence regulatory effectiveness across various jurisdictions. Drawing from academic databases including JSTOR, Scopus, and Web of Science, the review applies qualitative content analysis of peer-reviewed literature, focusing on legal frameworks, institutional roles, and sociocultural factors. Findings indicate significant regional differences in how legal systems balance statutory authority with ethical norms. European Union nations often implement value-driven regulations grounded in human rights and democratic accountability, while authoritarian regimes and postcolonial states face challenges due to institutional fragility and legal dualism. Institutions play a critical role in norm-setting and public trust, with successful cases demonstrating that moral legitimacy enhances legal compliance. Sociocultural factors further mediate the public’s response to laws, revealing tensions where formal law diverges from local values. Interventions such as EU compliance mechanisms and participatory justice reforms show promise in bridging the law-morality divide. The review underscores the urgency for systemic reform, advocating inclusive policy frameworks that integrate moral reasoning and community-based legal practices. These insights offer a roadmap for future research and policy interventions aimed at creating more just, culturally responsive legal systems.